2013
DOI: 10.1016/j.celrep.2013.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint Kinases Regulate a Global Network of Transcription Factors in Response to DNA Damage

Abstract: SUMMARY DNA damage activates checkpoint kinases that induce several downstream events, including widespread changes in transcription. However, the specific connections between the checkpoint kinases and downstream transcription factors (TFs) are not well understood. Here, we integrate kinase mutant expression profiles, transcriptional regulatory interactions, and phosphoproteomics to map kinases and downstream TFs to transcriptional regulatory networks. Specifically, we investigate the role of the Saccharomyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
95
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(110 citation statements)
references
References 52 publications
14
95
1
Order By: Relevance
“…5A), we identified 43 phosphorylation sites with a site probability of more than 75% within 89% sequence coverage. Sites which were also identified in previous studies (8,11,12,16) were differentially represented. Of these 43 high-confidence sites, 14 were S/T-P sites and 29 were non-S/T-P sites.…”
Section: Genotoxic Stress Affects Transcription Of G 2 /M-specific Gesupporting
confidence: 79%
See 1 more Smart Citation
“…5A), we identified 43 phosphorylation sites with a site probability of more than 75% within 89% sequence coverage. Sites which were also identified in previous studies (8,11,12,16) were differentially represented. Of these 43 high-confidence sites, 14 were S/T-P sites and 29 were non-S/T-P sites.…”
Section: Genotoxic Stress Affects Transcription Of G 2 /M-specific Gesupporting
confidence: 79%
“…Our study was instigated by observations made in Schizosaccharomyces pombe and mammalian cells, where transcription of genes promoting mitosis is known to be downregulated upon genotoxic stress treatment (13,14). Furthermore, global transcriptome analysis in the budding yeast revealed that methyl methanesulfonate (MMS)-treated mec1 and rad53 cells contain higher levels of G 2 /M-specific gene transcripts than wildtype cells (15,16). Nevertheless, until very recently, no further experimental evidence that would confirm these observations as well as the role of Mec1 or its downstream kinases, such as Rad53/ Chk1, in the regulation of G 2 /M transcription came forward.…”
mentioning
confidence: 99%
“…6D), though we have been unable to show direct phosphorylation of Ndd1 by either kinase, and therefore it remains a formal possibility that the DUN1/RAD53 dependence of these phosphorylations is indirect. As the manuscript was being prepared, the findings of a study that looked globally at changes to transcription factors in response to DNA damage were published (32). In further support of our model, this study (32) shows that transcription of the entire CLB2 cluster is downregulated in response to DNA damage and that the downregulation is fully dependent on RAD53 and partially dependent on DUN1.…”
Section: Discussionsupporting
confidence: 52%
“…For many of these clusters, the transcription factors targeted by the checkpoint machinery and the molecular mechanisms of the response have still not been worked out, although recent work has begun this effort (32). The regulation of these clusters is likely to be critical to the cell's ability to properly respond to DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Mec1 is a sensor kinase that, in concert with adaptor proteins such as Rad9 or Mrc1, phosphorylates downstream checkpoint targets, including the Rad53 and Chk1 transducing kinases (Melo and Toczyski 2002;Gobbini et al 2013; Bastos de Oliveira et al 2015). Following autophosphorylation and release from adaptors, Rad53 is thought to move throughout the cell to phosphorylate targets that promote cell cycle arrest, the inhibition of late-firing origins of replication, and a global transcriptional response (Melo and Toczyski 2002;Jaehnig et al 2013;Edenberg et al 2014a). While the DNA damage response is traditionally associated with phosphorylationbased signaling cascades, it has recently emerged that other post-translational modifications including ubiquitylation, sumoylation, and acetylation play prominent roles in the response in both yeast and other eukaryotes (Downey and Durocher 2006a;Psakhye and Jentsch 2012;Panier and Durocher 2013;Edenberg et al 2014a;Elia et al 2015).…”
mentioning
confidence: 99%